"Teaching Moments" in Psychotherapy: Addressing Emergent Life Events Using Strategies From a Modular Evidence-Based Treatment. Issue 1 (January 2019) - Guan, Karen; Boustani, Maya M.; Chorpita, Bruce F.
Abstract: Emergent life events (ELEs) are unexpected, acute client stressors reported in psychotherapy sessions that are associated with reduced evidence-based treatment (EBT) integrity and client progress. As a potential solution, this study examined the extent to which ELEs could be appropriately addressed using existing EBT strategies. Participants were 34 low-income youth (ages 5–15, 50% male, 85% Latino) seen by 18 therapy providers in the modular EBT condition (MATCH) of a community effectiveness trial. MATCH experts rated descriptions of 75 ELEs from therapy sessions on how well they might be addressed clinically by any of MATCH's 33 strategies for youth anxiety, depression, trauma, or conduct problems (i.e., "addressability"). MATCH-expert ratings were compared with observationally coded provider responses to ELEs. Results revealed that when assuming the presence of youth and caregiver in session, two-thirds of ELEs were identified as fully addressable and nearly all ELEs (96%) were partially addressable. ELEs related to family issues were most common but least likely to be addressable. Problem Solving and Relaxation skills could address the greatest percentage (87%) of ELEs. The most common supplemental content not explicitly prescribed in MATCH, but identified as necessary to fully address ELEs, was "assessing and empathic listening." Provider responses were often incongruent with MATCH-expert raters regarding which strategies to use for which ELEs. In summary, most ELEs reported in a diverse community sample could be theoretically harnessed as "teaching moments" for skills within an existing, multi-problem EBT. However, providers may benefit from development of a structured resource to guide them in choosing the most effective response when these unexpected events arise. Highlights: Evidence-based therapy strategies can often address emergent client stressors. Problem solving and relaxation skills address the greatest number of stressors. Assessment and empathy are also frequently recommended in response to stressors. Expert recommendations match therapists' responses to stressors half the time. Therapies may be improved by offering explicit guidance to manage client stressors.